Gastric teratoma in a 6-month-old boy - Peer Wildbrett; Hagen Graf Einsiedel; Björn Lange; Holger Lode; Winfried Barthlen (Wolters Kluwer Medknow Publications, 2012)
Gastric teratomas are very rare embryonal neoplasms, accounting for 2.6% of all perinatal diagnosed germ cell tumours. About 85% are well-differentiated mature lesions and about 15% are immature tumours with the potential of malignant transformation. The recommended therapy for gastric teratomas is surgical excision. We present the case of a 6-month-old boy with an incidentally detected epigastric mass. The histological examination revealed a mature gastric teratoma. The diagnostic imaging, therapy and postoperative follow-up are discussed.